Unknown makes unloved—A case study on improving integrated health and social care in the Netherlands using a participatory approach. (27th November 2019) - Lette, Manon; Boorsma, Marijke; Lemmens, Lidwien; Stoop, Annerieke; Nijpels, Giel; Baan, Caroline; de Bruin, Simone
Abstract: Many initiatives integrating health and social care have been implemented in order to provide adequate care and support to older people living at home. Further development of existing initiatives requires iterative processes of developing, implementing and evaluating improvements to current practice. This case study provides insight into the process of improving an existing integrated care initiative in the Netherlands. Using a participatory approach, researchers and local stakeholders collaborated to develop and implement activities to further improve collaboration between health and social care professionals. Improvement activities included interprofessional meetings focussing on reflection and mutual learning and workplace visits. Researchers evaluated the improvement process, using data triangulation of multiple qualitative and quantitative data sources. According to participating professionals, the improvement activities improved their communication and collaboration by establishing mutual understanding and trust. Enabling factors included the safe and informal setting in which the meetings took place and the personal relationships they developed during the project. Different organisational cultures and interests and a lack of ownership and accountability among managers hindered the improvement process, whereas issues such as staff shortages, time constraints and privacy regulations made it difficult to implement improvements on a larger scale. Still, the participatory approach encouraged the development of partnerships and shared goals on the level of both managers and professionals. This case study highlights that improving communication between professionals is an important first step in improving integrated care. In addition, it shows that a participatory approach, in which improvements are co‐created and tailored to local priorities and needs, can help in the development of shared goals and trust between stakeholders with different perspectives. However, stakeholders' willingness and ability to participate in such an improvement process is challenged by many factors.